Filtering push–pull power amplifier based on novel impedance transformers. Issue 17 (1st August 2016) - Zhang, Bo; Dong, Gaoya; Wu, Yongle; Yu, Cuiping; Liu, Yuanan
Abstract : A novel filtering push–pull power amplifier (PPPA), based on unbalanced‐to‐balanced impedance transformers, is presented for the first time. This novel impedance transformer can not only simplify the PPPA topology and miniaturise the overall circuit size, but also provide the bandpass filtering response and improve the second harmonic suppression performance. The proposed impedance transformers, which are constructed by two different C‐type line resonators, can provide good impedance matching performance under the odd‐mode excitation, while achieve high common mode suppression under the even‐mode excitation. Finally, a PPPA is designed and fabricated with the centre frequency of 2.45 GHz and bandwidth of 200 MHz for WLAN application. Moreover, detailed explanation and measured results are demonstrated for verification.